Patrons, clients, and policies patterns of democratic accountability and political competition - Kitschelt, Herbert 1955-; Wilkinson, Steven I. 1965- (Cambridge University Press, 2007)
Most models of party competition assume that citizens vote for a platform rather than narrowly targeted material benefits. However, there are many countries where politicians win elections by giving money, jobs, and services in direct exchange for votes. This is not just true in the developing world, but also in economically developed countries - such as Japan and Austria - that clearly meet the definition of stable, modern democracies. This book offers explanations for why politicians engage in clientelistic behaviours and why voters respond. Using newly collected data on national and sub-national patterns of patronage and electoral competition, the contributors demonstrate why explanations based on economic modernization or electoral institutions cannot account for international variation in patron-client and programmatic competition. Instead, they show how the interaction of economic development, party competition, governance of the economy, and ethnic heterogeneity may work together to determine the choices of patrons, clients and policies